Analisis Pengaruh Likuiditas Solvabilitas dan Provitabilitas Terhadap Nilai Perusahaan Sektor Healthcare di Bursa Efek Indonesia - Tantowi, Muhammad Ali (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2024)
This study aims to test whether liquidity, solvency, and provitability affect the value of healthcare (health) sector companies listed on the Indonesia Stock Exchange. The study took samples of health sector companies listed on the Indonesia Stock Exchange. The sampling method is a literature and documentation study, a sampling technique using the company's secondary data in the form of financial statements. Data collection is carried out through the company's financial statements for the period 2018-2021. The amount of data processed is as many as 56 company financial statements obtained from the Indonesia Stock Exchange through the www.idx.co.id website. Data analysis uses ratio analysis, classical assumption test, coefficient of determination test, and hypothesis test. The results showed that each independent variable had no influence on the dependent variable. This confirms that liquidity (current ratio), solvency (debt to equity ratio) and provitability (return on assets – return on equity) do not have a positive influence on the value of healthcare (health) sector companies listed on the Indonesia Stock Exchange.